Evaluation of HRMS Success Using DeLone & McLean - Heldha ayu Setia; Asif Faroqi; Virdha Rahma Aulia (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
Digital transformation has become a strategic step to improve operational efficiency, particularly in human resource management. PT XYZ, which has implemented HRMS, faces challenges such as system errors that disrupt the company's mission to enhance employee welfare. This study aims to evaluate the success of HRMS implementation at PT XYZ using the DeLone and McLean (2003) model, which includes six dimensions: system quality, information quality, service quality, usage, user satisfaction, and net benefits. A quantitative approach with PLS-SEM is used, and data is obtained through a survey. The sample consists of 211 respondents selected through simple random sampling. The analysis results show that system quality, information quality, and service quality significantly affect usage and user satisfaction, which contribute to the net benefits experienced by the organization. However, system quality does not significantly affect user satisfaction, and net benefits do not significantly affect usage. These findings provide insights for PT XYZ to improve the quality of HRMS and optimize system usage.